Total Quality Management – A Way to Manage Organizations Centred on Quality - Vasile Dinu (Amfiteatru Economic)
Following the consolidation and maturation of quality management, the evolution of this concept has demonstrated that its most advanced form has become Total Quality Management (TQM). Total Quality Management is a way of leading quality-centred organizations, as this is the main driving force that can direct the organization on the way to excellence in business. At the same time, it is based on the participation of all members, pursuing the efficiency of the long-term activity, leading to the effective satisfaction of the client, as well as to the benefits for all members of organization and for society. Total Quality Management is an approach that aims to continuously improve quality and performance to meet or exceed customer expectations. This can be accomplished by integrating all the functions and performance-related processes in a company. TQM targets all the quality improvement measures used by a company, including quality design and development, control, management, continuous improvement and quality assurance. In other words, TQM considers all quality measures at all levels and compartments that involve all employees in order to obtain long-term benefits